The Influence of Economic Literacy and Risk Perception on the Decision to Use Paylater with Paylater Benefits as a Moderation - Kamaruddin, Muhammad Junaid (Journal of Business and Behavioural Entrepreneurship, 2024)
This research is about "The Effect of Economic Literacy and Risk Perception on Purchasing Decisions Using Paylater with Paylater Benefits as Moderation". This research is motivated because there are still many Indonesians who still do not understand the Paylater payment method. This study occupies four variables consisting of variable Decision Using Paylater as the dependent variable. Economic Literacy and Risk Perception as independent variables. Furthermore, Benefit Paylater as a moderating variable. This study aims to prove whether there is an effect of economic literacy and risk perception on purchasing decisions using Paylater which is moderated by Paylater benefits. The research design uses causality which aims to test the direct effect and moderating effect between variables. The software used is SmartPLS (Partial Least Square). The results of this study are First, it shows that Economic Literacy has a significant effect on Purchasing Decisions Using Paylater, which means that based on this the hypothesis in this study is accepted. Second, Risk Perception has a significant effect on Purchasing Decisions Using Paylater, which means that based on this the hypothesis in this study is accepted. Third, it is stated that Benefit Paylater has a significant effect on Purchasing Decisions Using Paylater. Which means that based on this the hypothesis in this study is accepted. Fourth, Benefit Paylater strengthens the relationship between economic literacy on purchasing decisions using Paylater has a significant effect, which means that based on this the hypothesis in this study is accepted. Fifth, Benefit Paylater strengthens the relationship between Perception of Risk on Purchasing Decisions Using Paylater has a significant effect, which means that based on this, the hypothesis in this study is accepted.